The Meaning of וצבא גדול in Daniel 10,1 - Kuryliak, Ihor (2025)
The meaning of the phrase וצבא גדול in Dan 10,1 is disputed, variously translated as “but the time appointed was long,” “extremely hard to understand,” “great conflict” or “great war.” Based on linguistic and contextual evidence, this article provides new additional considerations for the meaning of וצבא גדול as “great host” or “great war.” The present paper sheds light on the complex nuances of וצבא גדול and shows its role in revealing the heavenly and earthly warfare described in Dan 10-12.
Keywords: Book of Daniel; Dan 10,1; great war; great conflict